Lactate and D-Dimer levels in acute pulmonary embolism and COVID-19 - Goktekin, Mehmet Cagri; Yilmaz, Mustafa (Bayrakol Medical Publisher, 2022)
Aim: This study aimed to compare clinical data and laboratory results in patients examined for suspected pulmonary embolism (PE) in the emergency department based on three groups: patients with coronavirus disease-2019 (COVID-19), patients with PE and patients with both COVID-19 and PE.Material and Methods: This retrospective study was approved by the local ethics committee of the university. Patients included in the study were divided into three groups: Group 1, consisting of COVID-19-polymerase chain reaction (PCR) (negative) and PE (positive) patients; Group 2, consisting of COVID-19-PCR (positive) and PE (negative) patients, and Group 3, consisting of COVID-19-PCR (positive) and PE (positive) patients.Results: The three patient groups included in the study had no difference in terms of age (p = 0.916) or sex. The laboratory results of the groups were compared using the Kruskal-Wallis test, which showed significant differences in the levels of white blood cells (p = 0.005), lymphocytes (p < 0.001), neutrophils (p = 0.016), D-Dimer (p < 0.001) and lactate (p = 0.001). Receiver operating characteristic curve analysis with a cut-off value of >2590 for D-Dimer showed 71.43% specificity and 78% sensitivity in differentiating Group 1 from Group 2, and with a cut-off value of >3640, it had 80% specificity and 81.82% sensitivity in differentiating Group 3 from Group 2.Discussion: COVID-19 leads to increased incidence of PE. In addition to clinical data, D-Dimer and lactate levels can be used in the differentiation of these patients.
Keywords: COVID-19; D-Dimer; Lactate; Pulmonary Embolism